Urgensi AMDAL sebagai persyaratan dalam sistem perizinan kegiatan perindustrian - Junaidi, Ahmad Khusnan (Maliki Interdisciplinary Journal, 2024)
The role of AMDAL in granting environmental permits has an important impact in preventing environmental damage and pollution. The function of AMDAL as a means of preventing environmental damage and pollution has changed after the ratification of the Job Creation Law, with its ideal concept as a tool to avoid the negative impact of a business or activity on the environment. The use of AMDAL is crucial in evaluating the impacts and consequences of planned activities on the environment. However, the elimination of AMDAL in the environmental licensing process regulated in the Job Creation Law is contrary to the principle of sustainable development because the focus is only on short-term interests. The main change in the Job Creation Law regarding AMDAL lies in licensing, which has now shifted to environmental approval. As a result, the process of assessing AMDAL documents has become irrelevant because the AMDAL assessment commission has been abolished. One of the main elements that must be of primary concern is licensing, because this can serve as a guide for businesses that will manage the environment. Environmental Impact Analysis (AMDAL) is a requirement for environmental licensing. Starting from the explanation above, the formulation of this research problem is (1) What is the licensing system for industrial activities in Indonesia? (2) What is AMDAL like in Indonesia? (3) How is AMDAL developed and supervised in Indonesia?